Efektivitas Model Pembelajaran Children Learning in Science (CLIS) dalam Pembelajaran IPA - Mulyani Mulyani; Agusminarti Agusminarti (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This study aims to examine in depth the effectiveness of the application of the Children Learning in Science (CLIS) learning model in the Natural Science (Science) learning process. The background of this study stems from the problem of low active student participation in class, which is largely caused by difficulties in understanding abstract science concepts. The CLIS model offers a learning approach that emphasizes active student involvement through a series of systematic learning stages. The method used is a literature review with a qualitative descriptive approach. Analysis was conducted on 25 articles from national and international publications. Each article was reviewed based on relevance, research methods, main findings, and the suitability of CLIS application in various science learning contexts. The results of the study indicate that CLIS has proven effective in improving students' understanding of science concepts, developing science process skills such as observation, classification, measurement, and hypothesis testing, and encouraging active student participation during the learning process. In addition, this model is also able to improve critical thinking skills through exploration activities, experiments, group discussions, and reflection on learning outcomes. The CLIS stages, which include exploring students' prior knowledge, introducing new concepts through experiments, strengthening understanding through discussions, and strengthening concepts through reflection, enable students to construct knowledge independently and meaningfully. Based on these findings, CLIS is considered relevant and can be an effective alternative learning model to improve the quality of science learning at various levels of education.